OTONOMI SEKOLAH PADA MASYARAKAT PESISIR, MENYONGSONG ASEAN ECCONOMY COMMUNITY (AEC) (Rekonseptualisasi Pokok Pikiran Ki Hadjar Dewantara Untuk Pendidikan Maluku Utara) - Irwan Djumat (EDUKASI, 2019)
School autonomy with its local curriculum as a sign for an area will provide opportunities for the region to develop its regional potential, including North Maluku, where most of the people live in coastal areas. Regional autonomy opens up space for the region to improve its education, and the coastal communities of North Maluku must be of special concern because of the potential of fisheries, coral reefs, mangrove forests, marine tourism islands, and others not touched by skilled hands, because they are not taught in education . Not to mention the local potential and cultural values of the people who are very very diverse which tend to be ignored. Even though all of this is the foundation supporting the national strength and integrity of the NKRI. Over time, the ASEAN Ecconomy Community (AEC) or the ASEAN Economic Community (MEA) was present and became a challenge for the people of North Maluku. If the education of the people of North Maluku is not qualified and ignores local values, then the output of education will be spectators and slaves in their own country. Ki Hadjar Dewantara has reminded us that "our culture is pressured by European culture; this is good, but even the big language seems to be hanging up ... The tools for reducing that language are: ... education, education for our children, for many people in our society.Key Words: Otonomi, local curriculum, asean ecconomy community